IMPLEMENTASI PENYALURAN DANA AKAD MURABAHAH PADA BMT-UGT SIDOGIRI KANTOR CABANG SURABAYA - Oktaviani, Mei Dia; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to find out how far the Baitul Maal wat Tamwil (BMT) of UGT Sidogiri as themicro syariah institution hold syariah values and principles in akad murabahah that has been set by the DSNMUI.The object of the research is the Baitul Maal wat Tamwil (BMT) of UGT Sidogiri office Surabaya branch.This research has been carried out by using qualitative approach and interpretative method. The data collectionhas been done by conducting interview and direct observation to the object of the research. The analysis has beencarried out by narrating the result of interview and direct observation. It has been found from the result of theresearch that the fatwa from the DSN-MUI about Murabahah particularly about the Akad Murabahah. TheBaitul Maal wat Tamwil (BMT) has represented it to their customer to purchase goods from the third parties,but the transaction of akad murabahah has been conducted before the goods has been bought and in principle thegoods has not belonged to the BMT. So the murabahah financing which has been carried out on the BMT hasbeen deviated from the guidelines that have been set by the National Islamic Council (BMT) through its fatwa asthe guidelines for Syariah banking in developing their financing productsKeywords: Implementation, murabahah, the fatwa of National Islamic Council-Indonesian Councilof Ulama, Baitul Maal wat Tamwil (BMT) of UGT Sidogiri